Capillary module haemodynamics and mechanisms of blood flow regulation in skeletal muscle capillary networks: Experimental and computational analysis. (22nd February 2022) - Mendelson, Asher A.; Ho, Edward; Scott, Shayla; Vijay, Raashi; Hunter, Timothy; Milkovich, Stephanie; Ellis, Christopher G.; Goldman, Daniel
Abstract : Abstract: The capillary module (CM), consisting of parallel capillaries from terminal arteriole to post‐capillary venule, is classically considered to be the building block of complex capillary networks. In skeletal muscle, CMs form interconnected columns spanning thousands of microns, which we recently described as the capillary fascicle. However, detailed evaluation of CM haemodynamics has not been described, and may provide insight into mechanisms of blood flow regulation in the microcirculation. We used intravital videomicroscopy from resting extensor digitorum longus muscle in rats ( n  = 9 networks, 112 capillary modules), as well as dual‐phase computational modelling of blood flow in simulated CM geometries. We found that the mean driving pressure across CMs was 3.236 ± 1.833 mmHg. Red blood cell (RBC) flow was independent of CM resistance, and the ratio of blood flow in adjacent modules was not correlated with their ratio of resistances. In simulated CM geometries, increases to driving pressure produced a direct linear increase to RBC and plasma flow, with no changes to RBC distribution; increases to arteriolar inflow haematocrit resulted in increased RBC flow, but with viscosity‐dependent increases to CM resistance. CM RBC flow heterogeneity was higher than plasma flow heterogeneity in experimental data, in contrast to simulated geometries, suggesting that time‐dependent flow variability may have important consequences for RBC distribution. In summary, these findings suggest that CMs are active participants in microvascular flow regulation, likely achieved through adjustments to CM driving pressure using pre‐ and post‐capillary loci of flow control. Increases to CM viscosity may be important during the regulation of functional hyperaemia. Key points: The capillary module (CM), consisting of parallel capillaries from the arteriole to venule, is classically considered to be the building block of capillary networks in skeletal muscle. A detailed evaluation of module haemodynamics may provide insight into mechanisms of blood flow regulation in the microcirculation. Using experimental data from resting skeletal muscle in rats, as well as dual‐phase computational models of blood flow, we analysed haemodynamic relationships and the impact of variations to boundary conditions on red blood cell and plasma distribution. We showed that driving pressure across CMs is low, and that simulated increases to inflow haematocrit have important viscosity‐dependent effects on module resistance. We found that red blood cell flow was independent from module resistance, which strongly suggests the regulation of driving pressure at the level of the capillary module using pre‐ and post‐capillary loci of flow control. These findings place CMs as central participants in microvascular flow regulation, with important consequences for disease and functional hyperaemia. Abstract : Abstract figure legend The mechanisms by which the microcirculation regulates skeletal muscle capillary blood flow are not well understood. We analysed capillary‐RBC haemodynamics and capillary network topology using intravital videomicroscopy of rodent skeletal muscle ( n  = 9 networks, 1491 capillaries, 112 capillary modules) and computational blood flow simulations of synthetic capillary modules. Haemodynamic relationships (pressure, flow, resistance) and boundary conditions (haematocrit, driving pressure, arteriole diameter) were evaluated. We found that capillary module driving pressure was low (3.236 ± 1.833 mmHg), and that capillary module RBC flow was independent of resistance for single modules and adjacent module pairs. Increases to inflow haematocrit in synthetic modules caused an increase in module viscosity and resistance. These findings suggest that capillary modules are active participants in microvascular flow regulation, likely through control of module driving pressure.